Moving beyond traditional therapies: the role of nanomedicines in lung cancer - Zhang, Jingjing; Li, Yanzhi; Guo, Sa; Zhang, Weifen; Fang, Bing; Wang, Shaohui (Frontiers in Pharmacology, 2024)
Amidst a global rise in lung cancer occurrences, conventional therapies continue to pose substantial side effects and possess notable toxicities while lacking specificity. Counteracting this, the incorporation of nanomedicines can notably enhance drug delivery at tumor sites, extend a drug's half-life and mitigate inadvertent toxic and adverse impacts on healthy tissues, substantially influencing lung cancer's early detection and targeted therapy. Numerous studies signal that while the nanocharacteristics of lung cancer nanomedicines play a pivotal role, further interplay with immune, photothermal, and genetic factors exist. This review posits that the progression towards multimodal combination therapies could potentially establish an efficacious platform for multimodal targeted lung cancer treatments. Current nanomedicines split into active and passive targeting. Active therapies focus on a single target, often with unsatisfactory results. Yet, developing combination systems targeting multiple sites could chart new paths in lung cancer therapy. Conversely, low drug delivery rates limit passive therapies. Utilizing the EPR effect to bind specific ligands on nanoparticles to tumor cell receptors might create a new regime combining active-passive targeting, potentially elevating the nanomedicines' concentration at target sites. This review collates recent advancements through the lens of nanomedicine's attributes for lung cancer therapeutics, the novel carrier classifications, targeted therapeutic modalities and their mechanisms, proposing that the emergence of multi-target nanocomposite therapeutics, combined active-passive targeting therapies and multimodal combined treatments will pioneer novel approaches and tools for future lung cancer clinical therapies.